DOES WORKFORCE DISCRIMINATION AND PERCEIVED LEADERSHIP STYLES RELATE WITH JOB SATISFACTION? - Nweke, Kingsley O; Dike-Aghanya, Adannia A; Okpara, Michael Okemuefula; Ilona, Chinenye F; Enike, Tobias C (Practicum Psychologia, 2019)
The study examined whether workforce discrimination and perceived leadership styles relate with job satisfaction of non teaching university staff. Participants for the study were 200 non teaching staff of Nnamdi Azikiwe University Awka, who were selected using simple random sampling technique. Two Instruments were used for data collection: Multifactor leadership questionnaire MLQ-5X and Minnesota Satisfaction Questionnaire (MSQ). The study adopted correlation design and statistics used for data management was Pearson Product Moment Correlation Coefficient. Result of the study showed that workforce discrimination did not significantly correlate with job satisfaction at r = -.01, and Transformational leadership style was also found to correlate highest than other leadership styles at r = .88, p < .01. It was recommendations that university school management should shun work-force discrimination among non-teaching staff.